Vowel insertion after coda plosives in the dialect of Paraíba (PB): reflections on the establishment of syllabic and social boundaries - Felipe Santos dos Reis; Rubens Marques de Lucena (Revista Investigações, 2020)
The present study aimed to verify how Brazilian Portuguese (BP) speakers born in the city of Campina Grande (PB) produce coda plosives in word-medial and -final positions, considering the possibilities of dealing with stray consonants in BP. Thus, 960 tokens of syllables closed by /p, t, k, b, d, g/ were recorded in audio and submitted for multivariate analysis. The results indicate that the application of the vowel insertion rule is influenced by two internal factors, namely the stray consonants and the words’ etymology, and two extralinguistic ones, that is, speakers’ gender and their L2 proficiency levels.